Performance Analysis of Optimization Techniques for PID Applications (International Journal of Advanced Research in Computer Science, 2017)
This paper represents the performance analysis of different optimization techniques. A performance index based on integral of absolute error, rise time, controller output and overshoot is given as an objective function of optimization, and genetic algorithm and other optimizations techniques are applied to optimizing parameters of PID controllers.Â Keywords: Genetic algorithm; PID controller; performance index; parameter optimization